Foucault’s Pendulum: the intellectuals and the Cuban Revolution (Andamios, Revista de Investigación Social, 2015)
The text examines the links between intellectual function and the project of the Cuban Revolution, by analyzing the main moments of this relationship and the approaches to it from power and the intellectual field, respectively. This analysis shows that such relationships can be understood by taking the interrelationships between the individual and the collective as a transversal axis; for example, between individual subjects related to intellectual function and the collective project, or between the revolutionary project and intellectual condition (collective) and intellectual function (individual). We also propose some central pairs for understanding the question, as the distinction between militant intelligentsia and intellectual militancy or cultural policy and politicized culture.
Keywords: Intellectuals; Cuban revolution; individual; collective; project